2014
DOI: 10.1590/0102-311x00138513
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência do papilomavírus humano (HPV) em Belém, Pará, Brasil, na cavidade oral de indivíduos sem lesões clinicamente diagnosticáveis

Abstract: HPV 6,11, 16, 18, 31, 33, 35, 52, and 58. HPV was present in 40 samples (24.1%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…In Brazil, a study conducted in Pará state reported HPV-18 to be the most frequent type with 12.5% prevalence. 6 High rates of HPV multiple infections in clinically healthy oral mucosa was also found by Terai et al 13 and Machado et al 3 with prevalence of 56.7% and 42.8%, respectively.…”
Section: Non-userssupporting
confidence: 59%
See 4 more Smart Citations
“…In Brazil, a study conducted in Pará state reported HPV-18 to be the most frequent type with 12.5% prevalence. 6 High rates of HPV multiple infections in clinically healthy oral mucosa was also found by Terai et al 13 and Machado et al 3 with prevalence of 56.7% and 42.8%, respectively.…”
Section: Non-userssupporting
confidence: 59%
“…This rate is similar to the one reported by Terai et al 13 in Japan (81%), but substantially different from those reported worldwide with a lower prevalence of the virus. 6,7,12 Little information is available regarding the prevalence of oral HPV infection in the Brazilian population. A study conducted with undergraduate students from a University in the state of Rio de Janeiro did not detect any virus in samples of healthy oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations